Intellectual property and access to medicines: mapping public attitudes toward pharmaceuticals during the United States-Mexico-Canada Agreement (USMCA) negotiation process - Anna S. Y. Wong; Clarke B. Cole; Jillian C. Kohler (BMC, 2021)
Abstract Background Transparency and accountability are essential components at all stages of the trade negotiation process. This study evaluates the extent to which these principles were upheld in the United States' public consultation process during the negotiation of the United States-Mexico-Canada Agreement (USMCA), with respect to public comments about the pharmaceutical sector and access to medicines. Results The public consultation process occurred before the start of official negotiations and was overseen by the Office of the United States Trade Representative (USTR). It included both written comments and oral testimony about US trade negotiation objectives. Of the written comments that specifically discussed issues relating to pharmaceuticals, the majority were submitted by private individuals, members of the pharmaceutical industry, and civil society organizations. Nearly all comments submitted by non-industry groups indicated that access to medicines was a priority issue in the renegotiated agreement, with specific reference to price affordability. By contrast, more than 50% of submissions received from members or affiliates of the pharmaceutical industry advocated for strengthened pharmaceutical intellectual property rights, greater regulatory data protections, or both. This study reveals mixed outcomes with respect to the level of transparency achieved in the US trade negotiation process. Though input from the public at-large was actively solicited, the extent to which these comments were considered in the content of the final agreement is unclear. A preliminary comparison of the analyzed comments with the USTR's final negotiating objectives and the final text of the USMCA shows that several provisions that were advanced exclusively by the pharmaceutical industry and ultimately adopted in the final agreement were opposed by the majority of non-industry stakeholders. Conclusions Negotiators could increase public transparency when choosing to advance one competing trade objective over another by actively providing the public with clear rationales for their negotiation positions, as well as details on how public comments are taken into account to form these rationales. Without greater clarity on these aspects, the public consultation process risks appearing to serve as a cursory government mechanism, lacking in accountability and undermining public trust in both the trade negotiation process and its outcomes.